Acceptance of artificial nesting sites by pollinating mason bees in commercial fruit plantations (Hymenoptera, Megachilidae: mixed Osmia cornuta and O. rufa population) - Benedek, P.; Nyéki, J.; Soltész, M.; Szabó, T.; Konrádné, C. (International Journal of Horticultural Science, 2010)
During a four yeas long experiment a simple bee shelterswas found to be a propermethod to increase the size ofmixed natural populations of the early season Osmia cornuta and O. rufa under practical farm conditions. Instead of the number of pesticide applications the earliness of the flowering of the fruit species in the orchards was found to be themost important factor in the rate of acceptance of reed as nestingmediumby Osmias in the bee shelter. This relationship was negative and highly significant (r = –0.829, p<0.001). This means that much higher acceptance of artificial nestingmedia in bee shelters and consequentlymuch higher population increase of the two early seasonmason bee species can be expected in orchards with early than with late flowering fruit species. Mixed orchards or early flowering orchards surrounded by other orchards falling in bloom later consecutively may also be much favourable to mason bees because they can find continuous food (pollen) supply there for a much longer time during their period of activity than in orchards planted with a single fruit species and being apart from orchards of other fruit species.